Make Short Answers Shorter: Support for the In Situ Approach. (16th July 2016) - Abe, Jun
Abstract: The standard approach for short answers is the one, like Merchant's (2004), in which the remnant phrase undergoes focus movement to a peripheral position before deletion takes place. In this article, I argue against this approach, supporting instead what we may call the in situ approach to short answers, according to which the remnant phrase does not undergo focus movement to a peripheral position but rather simply stays in its original position. Given the inescapable problem in testing island sensitivity in a wh ‐movement language such as English, this article investigates short answers in Japanese, a wh –in situ language. I propose that Japanese short answers are directly derived from what Hiraiwa & Ishihara (2002) call the no da in situ focus construction. This analysis immediately explains the island insensitivity of Japanese short answers. I also argue that the identification condition operative for licensing deletion in short answers is semantic in nature, hence compatible with the in situ approach that necessarily incorporates deletion of nonconstituents. Finally, I argue that the two strategies provided by Merchant (2004) for getting over the inescapable problem in testing island sensitivity in English are ill advised.